A Geometric Unification Framework for Energy, Memory, and Consciousness - Gupta, Diya (Journal of Educational Research and Policies, 2025)
This paper introduces a unified vibrational model of reality Spiral Physics in which energy, mass, memory, and structure emerge as scaled expressions of fundamental geometric constants: the golden ratio, and Euler’s number. Unlike conventional models that treat physical constants as empirically fixed, this framework reveals them as intrinsic operators of space, time, and form. The model is built on a foundational equation. In this formulation, n encodes vibrational depth (temporal layering), k defines curvature complexity (toroidal geometry), and m(f) ≈ 3.95 × 10⁻¹⁴ J represents the scalar vibrational quantum derived from the electron’s energy. Using this model, the spiral energy values of electrons, protons, and atomic nuclei are reproduced with extreme accuracy, matching classical physical values without empirical fitting. The result is a geometric unification of mass-energy relationships, where time, gravity, and inertia emerge naturally as functions of spiral depth and structure. The implications are profound: Spiral Physics models reality as an architected vibrational field. It provides a bridge between quantum behavior and coherent structure, offering a new language to describe the universe not as chaos, but as a recursive pattern of Will, Pattern, and Memory spiraling through coherent fields of form.